Social economy theoretical conceptualization (Revista de Investigaciones Universidad del Quindío, 2022)
Economics is a social science, which is responsible for studying and analyzing the way in which economic resources are used, be they families, companies, governments, among many other subjects, to know the way in which they are organized in the use of these, to meet their goals or objectives, as well as for their own satisfaction. Society is made up of a group of people, who have some relationship, living in the same place, which allows their interaction; The economy in social terms is a series of processes that aims to seek a social transformation, applied to various economic entities. The research work presented aims to describe by means of a descriptive methodology, to publicize the main structure of the social economy, demonstrating an adequate conceptualization of it, to have a better reasoning of the importance of the social economy, in the development of the individuals involved.
Keywords: social science; conceptualization; social economy